Effect of 1-methylcyclopropene on peel greasiness, yellowing, and related gene expression in postharvest ‘Yuluxiang’ pear - Li, Dan; Li, Xueling; Cheng, Yudou; Guan, Junfeng (Frontiers in Plant Science, 2023)
‘Yuluxiang’ pear (Pyrus sinkiangensis) is prone to greasy and yellowing during storage. In this study, 1-methylcyclopropene (1-MCP) with 1.0 μl L-1 was applied in ‘Yuluxiang’ pear to investigate its effects on fruit quality, peel wax and greasy index as well as chlorophyll content, and the expression pattern of the related genes during storage at ambient temperature (25 °C). The results showed that 1-MCP treatment maintained higher fruit firmness and chlorophyll content, decreased respiration rate and postponed the peak of ethylene production rate, lowered the greasy index of the peel. The contents of wax components, such as the three alkenes (C23, C25, C29), three fatty acids (C16, C18:1, C28), three aldehydes (C24:1, C26:1, C28:1) and six esters (C22:1 fatty alcohol-C16 fatty acid, C22:1 fatty alcohol-C18:1 fatty acid, C22 fatty alcohol-C16 fatty acid, C22 fatty alcohol-C18:1 fatty acid, C24:1 fatty alcohol-C18:1 fatty acid, C24 fatty alcohol-C18:1 fatty acid), significantly increased with the extension of storage time, and the expression of genes associated with ethylene biosynthesis and signal transduction (ACS1, ACO1, ERS1, ETR2, and ERF1), chlorophyll breakdown (NYC1, NOL, PAO, PPH, SGR, and WRKY75-1) and wax synthesis (LACS1, LACS6, KCS1, KCS2, KCS4, KCS10L, KCS11L, KCS20, FDH, CER10, KCR1, ABCG11L, ABCG12, ABCG21L, LTPG1, LTP4, CAC3, CAC3L, and DGAT1L) upregulated in the earlier stage of storage, while they were reduced by 1-MCP treatment. There was close relationship among the main wax composition (alkane, alkene, fatty acids, esters, aldehydes, and fatty alcohols), chlorophyll content, greasy index, and expression level of genes associated with chlorophyll breakdown and wax synthesis. These results suggested that 1-MCP treatment decreased the wax content, greasiness and yellowing by inhibiting effects of ethylene synthesis, signal transduction, chlorophyll degradation and wax synthesis in ‘Yuluxiang’ pear.